Empagliflozin in posttransplantation diabetes mellitus: A prospective, interventional pilot study on glucose metabolism, fluid volume, and patient safety. Issue 3 (25th January 2019) - Schwaiger, Elisabeth; Burghart, Lukas; Signorini, Lorenzo; Ristl, Robin; Kopecky, Chantal; Tura, Andrea; Pacini, Giovanni; Wrba, Thomas; Antlanger, Marlies; Schmaldienst, Sabine; Werzowa, Johannes; Säemann, Marcus D.; et al.
Abstract : The safety and efficacy of sodium‐glucose cotransporter 2 inhibitors in posttransplantation diabetes mellitus is unknown. We converted stable kidney transplant patients to 10 mg empagliflozin, aiming at replacing their insulin therapy (<40 IU/d). N = 14 participants (the required sample size) completed the study visits through 4 weeks and N = 8 through 12 months. Oral glucose tolerance test (OGTT)–derived 2‐hour glucose (primary end point) increased from 232 ± 82 mg/dL (baseline) to 273 ± 116 mg/dL (4 weeks, P = .06) and to 251 ± 71 mg/dL (12 months, P = .41). Self‐monitored blood glucose and hemoglobin A1c were also clinically inferior with empagliflozin monotherapy, such that insulin was reinstituted in 3 of 8 remaining participants. Five participants (2 of them dropouts) vs nine of 24 matched reference patients developed bacterial urinary tract infections ( P = .81). In empagliflozin‐treated participants, oral glucose insulin sensitivity decreased and beta‐cell glucose sensitivity increased at the 4‐week and 12‐month OGTTs. Estimated glomerular filtration rate and bioimpedance spectroscopy‐derived extracellular and total body fluid volumes decreased by 4 weeks, but recovered. All participants lost body weight. No participant developed ketoacidosis; 1 patient developed balanitis. In conclusion, although limited by sample size and therefore preliminary, these results suggest that empagliflozin can safely be used as add‐on therapy, if posttransplant diabetes patients are monitored closely (NCT03113110). Abstract : Empagliflozin appears safe, but exerts a weak antihyperglycemic effect, suggesting that the drug should be used as add‐on therapy under close medical supervision in patients with stable post–kidney transplantation diabetes mellitus.